The role of organisational memory for learning in project management using lessons learned : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Business Studies in Human Resource Management at Massey University - Gosling, Isobelle Anne (Massey University, 2000)
The notion of learning from experience framed as lessons learned (an output of project management practice) stored in organisational memory has been little discussed in the literature. Prolifically discussed is organisational learning to build capability through generative learning to achieve what an organisation desires. Organisational memory is the fundamental result of organisational learning to store the knowledge from the past that is 'brought to bear' on the activity to hand by means of acquisition, retention, search and retrieval processes. It is argued the storage of lessons learned in human memory and the sharing of lessons learned between projects significantly contributes to project success at the personal level, but not at the organisational level despite lessons learned shared generically. This argument is supported by the strong suggestions of systematic problem solving to get at the 'root' cause, continuous improvement embedded in practice through benchmarking, quality management, flexibility in using standardised tools, the moderate suggestion of an Organisational Memory Management System (OMIS), and project strategic support. These were the findings from a survey of 47 project practitioners at two Project Management Institute (PMI) meetings, and seven semi-structured interviews where participants perceived the organisation they worked in characterised organisational learning practices. These findings raise questions about the competitive advantages for the organisation by using lessons learned, a moderate to weak finding in this study, and the recent initiative by most participants to implement an OMIS system. It is recommended project practitioners make lessons learned an everyday project management practice to build capability to advance organisational learning, or else the lessons learned will be pushed aside by time constraints and the pressure to move onto new projects. Key Concepts: Lessons learned, organisational learning, and organisational memory.
Keywords: Organisational learning; Project management